The influence of noise on net revenue and values of investment properties: Evidence from Switzerland - Stefan Sebastian Fahrländer; Michael Gerfin; Manuel Lehner (University of Bern, Department of Economics, 2015)
In this study we use hedonic models to measure the influence of noise nuisance on rents, costs and values of investment properties in Switzerland. Countrywide data is provided by institutional real estate investors. The effects are measured for aircraft noise, road traffic noise and railroad noise. We show that negative effects appear between lower and upper tresholds which vary between different noise types and across residential and non-residential properties. Rents, costs and values are affected below the administrative tresholds given by the LSV and the negative impact ceases at an upper threshold. However high noise nuisance might influence investment decisions, i.e. offices are built instead of housing etc. These important effects are not given account in the data. In addition, directly measured reductions on market values are lower than the expected reductions based on empirical effects on rents and costs. The reasons for the different market value reductions may be found in the Swiss tenancy law. Rents for dwellings within existing rental agreements can only be adjusted in accordance with the change of the "reference interest rate" (Referenzzinssatz) and the CPI. The analysis shows that the average contract duration is dependent on the noise nuisance, which leads to a significant reduction of noise-induced losses within periods of increasing market rents.
Keywords: 330; hedonic prices; investment property; Switzerland; noise nuisance; GAM; spline